Stably transfected adherent cancer cell models with decreased expression of 5′-nucleotidase cN-II. (1st December 2016) - Bricard, Gabriel; Cros-Perrial, Emeline; Machon, Christelle; Dumontet, Charles; Jordheim, Lars Petter
ABSTRACT: The 5′-nucleotidase cN-II has been shown to be associated with the sensitivity to nucleoside analogues, the survival of cytarabine treated leukemia patients and to cell proliferation. Due to the lack of relevant cell models for solid tumors, we developed four cell lines with low cN-II expression and characterized them concerning their in vitro sensitivity to cancer drugs and their intracellular nucleotide pools. All four cell models had an important decrease of cN-II expression but did not show modified sensitivity, cell proliferation or nucleotide pools. Our cell models will be important for the study of the role of cN-II in human cancer cells.